2003
DOI: 10.1016/s0925-4439(03)00035-8
|View full text |Cite
|
Sign up to set email alerts
|

URP1: a member of a novel family of PH and FERM domain-containing membrane-associated proteins is significantly over-expressed in lung and colon carcinomas

Abstract: In a concerted effort to identify biomarkers for lung and colon carcinomas by genome-wide transcriptional profiling, we describe the identification and cloning of one such gene as well as two additional closely related genes. Due to the strong sequence homology to the C. elegans UNC-112 we call this gene URP1, for UNC-112 related protein. We have also isolated the full-length clones for another novel related gene, URP2 and the previously discovered MIG-2 gene. Collectively, these proteins, together with two fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
65
1
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 30 publications
1
65
1
1
Order By: Relevance
“…Furthermore, cell spreading is perturbed upon reduction of kindlerin protein. Taken together with the observation that kindlerin is overexpressed in colon and lung carcinomas (2), our data support a role for kindlerin in mammalian cell adhesion and suggest that kindlerin may mediate TGF-␤ signaling in tumor progression via contributions to integrin-dependent cellular functions.…”
supporting
confidence: 81%
See 2 more Smart Citations
“…Furthermore, cell spreading is perturbed upon reduction of kindlerin protein. Taken together with the observation that kindlerin is overexpressed in colon and lung carcinomas (2), our data support a role for kindlerin in mammalian cell adhesion and suggest that kindlerin may mediate TGF-␤ signaling in tumor progression via contributions to integrin-dependent cellular functions.…”
supporting
confidence: 81%
“…ent with our findings on kindlerin and supports a general role for the Mig-2 family in cell adhesion. To date, no reports have described URP2 function; however, its high expression levels in spleen, thymus, and peripheral blood leukocytes suggest a role specific to the immune system (2). Future experiments will be needed to address the role of the enrichment of kindlerin at membrane ruffles and sites of cell-cell contact in altered adhesion, migration, and morphology of TGF-␤-treated cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors speculated that MIG2 is overexpressed on the transcriptional level, and that MIG2 could be involved in hormone-mediated growth. Weinstein and colleagues found that expression patterns for the three protein family members, MIG2, URP1, and URP2 differed among various tumor tissues (13). The authors reported that URP1 expression was increased in 70% of colon and 60% of lung carcinomas, but was not increased in breast carcinomas.…”
Section: Discussionmentioning
confidence: 99%
“…MIG2 belongs to a newly recognized protein family comprising URP1, URP2 and the Caenorhabditis elegans protein, UNC-112, which all share a unique protein structure consisting of two 4.1-ezrinradixin-moesin domains flanking a pleckstrin homology domain (13,14). MIG2 has been further characterized as a component of cell-ECM adhesion sites and described its involvement in controlling cell shape and spreading (15).…”
Section: Introductionmentioning
confidence: 99%